PERSEPSI DOSEN AKUNTANSI PERGURUAN TINGGI DI JAKARTA ATAS IMPLEMENTASI MATERIAL FLOW COST ACCOUNTING (MFCA) - Juniati Gunawan; Riana Lestari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this study is to determine the perception of accounting lecturers in Universities across Jakarta on the implementation of material flow cost accounting (MFCA). The variables in this study are the perception of accounting lecturers in Jakarta and MFCA implementation. The data was obtained using purposive sampling method and a survey questionnaire answered by accounting lecturers of various Universities in Jakarta. The samples used were 180 questionnaires. The analysis technique used is Mann-Whitney. The results indicates a positive response from accounting lecturers in Jakarta, that this is the time for Universities with accounting program to hold an environment accounting class and companies to implement MFCA. The results of subsequent studies indicate that there are differences in the perception of accounting lecturer between the big and the small Universities in Jakarta on the implementation of MFCA.